The Results of Enrichment of Samples of Ore Deposits Eshlik Using the Traditional and Local SI Reagent - Salijanova Gulnoraxon Kaxarovna; Mirkhamidova Dilnavozi O’tkir kizi (Genius Publishing Group, 2022)
In job the results of study of material structure and enrichment of tests of ores of deposits Eshlik are given. As a result of the studies, recommended regimens for enrichment of ores were developed using a combination of a traditional collector and “CI” at a flow of 50% of the mixture of xantogenes and concentrates of higher quality were obtained
Keywords: Enrichment; material structure; analysis; chemical analysis